Role of neuronal nicotinic acetylcholine receptors in cannabinoid dependence - Belle Buzzi; Eda Koseli; Lauren Moncayo; Mohammed Shoaib; M Imad Damaj (Elsevier, 2023)
Cannabis is among the most widely consumed psychoactive drugs around the world and cannabis use disorder (CUD) has no current approved pharmacological treatment. Nicotine and cannabis are commonly co-used which suggests there to be overlapping neurobiological actions supported primarily by the co-distribution of both receptor systems in the brain. There appears to be strong rationale to explore the role that nicotinic receptors play in cannabinoid dependence. Preclinical studies suggest that the ɑ7 nAChR subtype may play a role in modulating the reinforcing and discriminative stimulus effects of cannabinoids, while the ɑ4β2 * nAChR subtype may be involved in modulating the motor and sedative effects of cannabinoids. Preclinical and human genetic studies point towards a potential role of the ɑ5, ɑ3, and β4 nAChR subunits in CUD, while human GWAS studies strongly implicate the ɑ2 subunit as playing a role in CUD susceptibility. Clinical studies suggest that current smoking cessation agents, such as varenicline and bupropion, may also be beneficial in treating CUD, although more controlled studies are necessary. Additional behavioral, molecular, and mechanistic studies investigating the role of nAChR in the modulation of the pharmacological effects of cannabinoids are needed.